Membraneless Plant Microbial Fuel Cell using Water Hyacinth (Eichhornia crassipes) for Green Energy Generation and Biomass Production - Widharyanti, Ika Dyah; Hendrawan, Muhammad Andiri; Christwardana, Marcelinus (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
The plant microbial fuel cell (PMFC) is a technology built to produce renewable and sustainable electricityin order to meet the increasing global demand. This study demonstrates the potential application of PMFC in swamps dominated by water hyacinth to produce biological energy and plant biomass.In this research, the plant was integrated into a microbial fuel cell that adopts various types of anode materials such as carbon felt, iron and zinc, with a varying distance of 10 and 20 cm between the anode and cathode. Organic compounds emerging from the photosynthesis process were deposited by plant roots, which were then oxidized by bacteria in the mud media. The result showed that the developed PMFC produced a voltage and current density of 244.8 mV and 185.4 mA/m2, respectively, for 30 days, with a maximum power of 100.2 mW/m2 in the cells using zinc as anode material with an electrode spacing of 10 cm. Furthermore, the pH value on PMFC with a longer electrode was higher than the shorter distance due to the protons' inability to move from anode to cathode against the force of gravity. In conclusion, PMFC which utilizes water hyacinth has a good performance in converting chemical energy from the substrate into electrical energy, and has the potential to be developed in underdeveloped areas.